HS-SPME-GC-MS determination of the scent of Anacamptis taxa (fam. Orchidaceae) from Basilicata (Southern Italy) - D'Auria, Maurizio; Emanuele, Lucia; Lorenz, Richard; Mecca, Marisabel; Racioppi, Rocco; Romano, Vito Antonio; Viggiani, Licia (Natural product research, 2024)
The scent of Anacamptis species has been analyzed by using HS-SPME-GC-MS. The sample was collected in Basilicata (Southern Italy). Every species showed a different composition of the scent in the analyses we performed. 1,2,4-Trimethoxybenzene and methyl 4-mehoxybenzoate were the main components of that of Anacamptis coriophora subsp. fragrans. The scent of Anacamptis laxiflora was due to the presence of caryophyllene. Linear hydrocarbons but also decanal were components of the scent of Anacamptis pyramidalis. Eucalyptol was found in the scent of Anacamptis papilonacea. Finally, β-sesquiphellandrene was the main component of the scent of Anacamptis morio.